Utilização do delineamento de misturas de caulim, resíduo do caulim e alumina para obtenção de cerâmicas à base de mulita - Alves, Hugo Plínio de Andrade (2016)
Refractory ceramics are ceramic materials which have among its main features the ability to withstand high temperatures without melting or decomposed and to remain non-reactive and inert when exposed to harsh environments. These characteristics define the purposes for which these materials are proposed, which can be highlighted applications linings, heat treatment and refining of metals, manufacture of glass and power generation. With the constant evolution of the refractory industry, increasingly necessary it becomes the search for technological means to bring improvements to the cost / benefit ratio of the materials produced. The use of natural raw materials is a point of extreme importance in the refractory industry, since these raw materials are found in deposits scattered in the earth's crust. The mullite (3Al2O3.2SiO2) is an alumino-silicate that due to its special properties has been described as one of the most important refractory ceramic of today. The kaolin waste obtained in the second step of the primary kaolin processing can be used as a source for synthesizing mullite. In this context, this study aimed to use the mixture design (kaolin, kaolin waste and alumina) to obtain mullite based refractory ceramics. The samples were pressed and sintered between 1300 and 1550 °C and then subjected to the determination of physical and mechanical properties, characterization of crystalline phases by XRD and microstructural analysis by SEM. The results indicated obtaining mullite from 1300 °C. It was observed that the mullitization process was affected by the concentration of the raw materials and the sintering temperature. In compositions rich in kaolin waste the sintering mechanism by liquid phase favors the densification process. A specific formulation, containing 50 wt.% of kaolin and 50 wt.% of kaolin waste (mica-rich) had twice the mechanical strength of pure kaolin after sintering at 1300 °C. This study demonstrated the possibility of obtaining mullite with up to 94% of relative density through reactive sintering of kaolin/residue kaolin/alumina mixtures at temperatures as low as 1300 °C.